Dimension Effect of Tangibles, Reliability, Responsiveness, Assurance, Empathy, Leadership towards Employee Satisfaction - Martini, Luh Kadek Budi; Suardana, Ida Bagus Raka; Astawa, I Nengah Dasi (International Research Journal of Management, IT & Social Sciences, 2018)
The present research was intended for analyzing dimension effect of tangibles, reliability, responsiveness, assurance, empathy, and leadership towards employee satisfaction in the University. The objective research was the head office of Public University in Bali. It was a limited population of the civil servants whose minimal working time was one year. The number of samples in the present research was 185. The sampling technique used was stratified proportional random sampling. Data analysis was conducted by using structural equation model supported with AMOS 20.0. The results of data analysis were obtained that only dimension of empathy mastering a significant effect on satisfaction for an internal customer in the University in Bali.